Effect of TiO2 Abutment Coatings on Peri-Implant Soft Tissue Behavior: A Systematic Review of In Vivo Studies - Areid, Nagat (Hidawi, 2025)
Establishing a proper soft tissue adhesion around the implant abutment is essential to prevent microbial invasion, inhibit epithelial downgrowth, and obtain an optimal healing process. This systematic review aims to evaluate the real potential of TiO2 coating on the behavior of peri-implant soft tissue health and maintenance. A specific aim was to evaluate clinically and histologically the effect of TiO2 abutment coating on epithelial and connective tissue attachment. Electronic database searches were conducted from 1990 to 2023 in MEDLINE/PubMed and the Web of Science databases. In total, 15 out of 485 publications were included. Eight studies involved humans, and seven were animal studies. Exposure time ranges from 2 days to 5 years. The peri-implant soft tissue evaluations included clinical assessment (plaque index (PI), peri-implant probing pocket depth (PPD), and bleeding on probing (BoP)), histological as well as histomorphometric analysis. The Office of Health Assessment and Translation (OHAT) Risk of Bias Rating Tool for Human and Animal Studies was used to evaluate the overall quality of the studies included in the review. The results showed some variation but remained within acceptable limits. Within the limitations of this systematic review, the present findings suggest that TiO2 coatings seem to influence soft tissue healing. TiO2-coated abutments with a roughness value between 0.2 and 0.5 μm enhance soft tissue health. Sol-gel-derived TiO2 coatings induced better soft tissue attachment than noncoated machined abutment surfaces. The anodized titanium abutments demonstrate comparable clinical and histological outcomes to conventional machined abutments. However, there was variation among the included studies concerning TiO2 coating characteristics and the measured outcomes used to evaluate the soft tissue response, and therefore, quantitative analysis was not feasible. Long-term in vivo studies with standardized soft tissue analysis and coating surface parameters are necessary before a definitive conclusion can be drawn. OSF Registration No.: 10.17605/OSF.IO/E5RQV.